Psychometric properties of the newly developed Physician Teaching Self-Efficacy Questionnaire (PTSQ). Issue 1 (December 2016) - Dybowski, Christoph; Kriston, Levente; Harendza, Sigrid
Abstract Background High teaching quality and students' corresponding learning progress are the most important indicators of teachers' work performance. Theory and numerous empirical studies indicate that self-efficacy, a person's belief in her or his ability to accomplish a task, is an important predictor of work performance. Accordingly, it can be assumed that teaching self-efficacy also influences teaching performance and students' learning progress with regard to physicians who teach in undergraduate medical education. Therefore, the aim of this study was to develop and validate an instrument measuring clinical teaching self-efficacy in physicians. Methods We developed 16 items reflecting physicians' beliefs to provide high quality clinical teaching when facing regularly occurring critical teaching situations. These constitute the Physician Teaching Self-Efficacy Questionnaire (PTSQ). For its validation, we used data from a sample of 247 physicians from internal medicine and surgery at six German medical faculties. Regarding factorial validity, we performed exploratory structural equation modelling (ESEM) as well as confirmatory factor analysis (CFA). Regarding criterion validity, correlations with the scales of the Physician Teaching Motivation Questionnaire (PTMQ), teaching experience and perceived teaching involvement were calculated. Additionally, we conducted the same analyses with a short 6-item version. Results ESEM delivered evidence for a three-factor structure with a superordinate general factor, which was confirmed by local and global fit indicators in CFA (RMSEA = .055, TLI = .939, SRMR = .048, CFI = .948). We identified the following three subfactors: teaching self-efficacy with respect to self-regulation, dyadic regulation involving students, and triadic regulation involving students and patients. Internal consistencies indicated acceptable to excellent reliability for all scales (Cronbach's alpha = .77–.90). Theory-consistent correlations with the PTMQ scales, teaching experience, and teaching involvement confirmed criterion validity. Besides excellent global fit, the short version of the PTSQ also fulfilled all other validity criteria. Conclusions The PTSQ is a valid instrument to assess physicians' clinical teaching self-efficacy. It could be used in faculty development programmes and for educational research. The short version could be used in situations that are time-critical for physicians in order to ensure high response rates.